2006
DOI: 10.1038/sj.onc.1209702
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of BAK by butyrate in the colon is associated with increased Sp3 binding

Abstract: Butyrate is a key bioactive product of dietary fibre fermentation thought to play a key role in cancer prevention. One contributory mechanism in this role is the regulation of apoptosis by butyrate. As butyrate shows low levels of toxicity, the mechanisms by which it triggers or regulates apoptosis are of great interest. We and others have shown that the proapoptotic protein BAK is upregulated by butyrate. We show here that this observation is conserved across multiple cell lines, that it occurs in all cells i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
69
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(75 citation statements)
references
References 33 publications
6
69
0
Order By: Relevance
“…TSA has also been described to modulate the acetylation of Sp1 and subsequently upregulate transcription of transforming growth factor type II receptor gene (26). GC-rich regions of promoter sequences have previously been shown to be activated by butyrate through Sp1 or Sp3 binding (7,13,42). Interestingly, one such putative Sp1 binding site was found in the butyrate and TSA-responsive element within the 0.5 kb fragment of ANGPTL4 promoter (at position Ϫ362).…”
Section: Discussionmentioning
confidence: 94%
“…TSA has also been described to modulate the acetylation of Sp1 and subsequently upregulate transcription of transforming growth factor type II receptor gene (26). GC-rich regions of promoter sequences have previously been shown to be activated by butyrate through Sp1 or Sp3 binding (7,13,42). Interestingly, one such putative Sp1 binding site was found in the butyrate and TSA-responsive element within the 0.5 kb fragment of ANGPTL4 promoter (at position Ϫ362).…”
Section: Discussionmentioning
confidence: 94%
“…Expression of Puma for instance can also be induced by FoxO3 and SP1. 26,27 Interestingly, Chirakkal et al 28 identified a SP1-binding site within the bak1 promoter that was also indicated in our MatInspector analysis (Figure 1). This SP1-binding site mediates upregulation of Bak in response to butyrate as well as basal Bak expression.…”
Section: Discussionmentioning
confidence: 96%
“…This can reduce the burden of carcinogens, such as BAs, and therefore decrease the number of mutations, which reduces cancer risk. Experimental studies have shown that it regulates colonic epithelial growth and protects against carcinogenesis by inhibiting the proliferation and migration of neoplastic cells, restricting tumor angiogenesis, inducing apoptosis, and promoting differentiation of the neoplastic colonocytes (43)(44)(45)(46)(47)(48)(49). F. prausnitzii, a member of Clostridium cluster IV, is one of the most dominant butyrate producers, but also may have independent antiinflammatory properties related to secreted metabolites, which have been shown to block nuclear factor kB activation and IL-8 production (50).…”
Section: Discussionmentioning
confidence: 99%